Clinical Anatomy and Embryology A Guide for the Classroom, Boards, and Clinic - Leo, Jonathan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is written for medical and other allied health students. It seeks to aid students in gaining a general understanding of clinical anatomy before embarking on a specific discipline-focused program. Organized among two sections, the first includes chapters that cover the anatomy of the head and neck, abdomen, thorax, pelvis and perineum, lower limb, upper limb, and back. What$1 (Bs more, section two briefly examines the embryology and development of the organ systems, such as the development of major organs. This title is an invaluable resource for students who wish to retain anatomical knowledge on the entire human body despite an eventual career in one particular discipline of medicine. It is complemented by its previously published sister text Medical Neuroanatomy for the Boards and the Clinic, which applies similar principles of anatomical information with a focus on identifying potentially malignant lesions. .s
Section One Clinical Anatomy -- Chapter One: Head and Neck -- Chapter Two: Abdomen -- Chapter Three: Thorax -- Chapter Four: Pelvis and Perineum -- Chapter Five: Lower Limb -- Chapter Six: Upper Limb -- Chapter Seven Back -- Section Two Embryology -- Chapter Eight: The first three week of Development -- Chapter Nine: Development of Major Organs.
Keywords: Medicine; Medical education; Clinical Medicine; Medical Education; Anatomy; Embryology